Impact of the COVID-19 Pandemic on Human Papillomavirus Vaccination in Brazil - Tércia Moreira Ribeiro Da Silva; Ana Carolina Micheletti Gomide Nogueira de Sá; Mark Anthony Beinner; Mery Natali Silva Abreu; Fernanda Penido Matozinhos; Ana Paula Sayuri Sato; Ed Wilson Rodrigues Vieira (Frontiers Media S.A., 2022)
Objective: To analyze the number of applied HPV vaccine doses before (from April 2019 to March 2020) and after (from April 2020 to September 2020) social distancing measures in response to the COVID-19 pandemic in states and regions of Brazil.Methods: Ecological time-series study, using data from the Brazilian National Immunization Program (PNI). Using the Mann-Whitney test, we evaluated the difference between the median number of applied doses during the periods April 2019 to March 2020 and from April 2020 to September 2020. Spatial analysis identified clusters with a high or low percentage reduction in the median applied doses. Prais-Winsten regression models identified temporal trends in the applieddoses from both periods.Results: There was a significant reduction in the median HPV vaccine doses applied, formation of spatial clusters and, after a sharp drop in the number of applieddoses during the months following social distancing. There was a tendency to increase the applied vaccines doses.Conclusion: The COVID-19 pandemic resulted in reduction of the number of HPV vaccine doses applied as a possible effect of restrictive measures caused by the pandemic.